The Effect of Personal Words Notes on Enhancing Students’ Vocabulary Mastery - Nur Fadila; Geminastiti Sakkir; Hasriani G (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This exercise aims to find out how personal word notes affect students' vocabulary. This study used a one-group pre- and post-test experimental design with a focus on quality. According to research, students at MTs Babussalam can use Personal Words Notes (PWN) in class, based on the findings and discussion of chapters and findings of papers. The purposive sample that suits the two students is different. Test data (both after and after the test) are collected. The results show that the